If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10y + -6 = 4y + 8 Reorder the terms: -6 + 10y = 4y + 8 Reorder the terms: -6 + 10y = 8 + 4y Solving -6 + 10y = 8 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. -6 + 10y + -4y = 8 + 4y + -4y Combine like terms: 10y + -4y = 6y -6 + 6y = 8 + 4y + -4y Combine like terms: 4y + -4y = 0 -6 + 6y = 8 + 0 -6 + 6y = 8 Add '6' to each side of the equation. -6 + 6 + 6y = 8 + 6 Combine like terms: -6 + 6 = 0 0 + 6y = 8 + 6 6y = 8 + 6 Combine like terms: 8 + 6 = 14 6y = 14 Divide each side by '6'. y = 2.333333333 Simplifying y = 2.333333333
| 8h=26 | | 7-(2z-5)=6-3z | | 2/3y+v=x | | v-9=214 | | 16+8x=25+15+3 | | -13x-13=2x-46 | | 220=4(-2+7x)+4 | | y=2/3(7)+4 | | -8(1+7m)=384 | | 0=4(4t^2+16t-7) | | 3.50+2.50x=25 | | -15+m/4=-11 | | -11n+16=-10n-5 | | -4(2-c)=12 | | -3(4r+-8)=-36 | | 49/98=a/112 | | 2/5+4/7 | | y=2/3(5)+4 | | 13.95x+1.95=85.95 | | (-2/x-3)+(3/x+3)=(-12/x^2-9) | | -7-y-y=-1 | | Ab+3c=2 | | r-5.20=3.50 | | 0.3(x+80)+1.5x=105 | | n/3-10=-6 | | y=(c-d)x+6 | | -4(x-6)=-(x-7) | | 4/5x-3=x-1/3 | | x+24+4x=-21-4x-27 | | 7y=-7y | | 8(x-3)+6= | | 25+4x^2=-20x |